2023
DOI: 10.1186/s12959-023-00475-6
|View full text |Cite
|
Sign up to set email alerts
|

Platelet indices and blood pressure: a multivariable mendelian randomization study

Abstract: Background Platelet indices are blood-based parameters reflecting the activation of platelets. Previous studies have identified an association between platelet indices and blood pressure (BP). However, causal inferences are prone to bias by confounding effects and reverse causation. We performed a Mendelian randomization (MR) study to compare the causal roles between genetically determined platelet indices and BP levels. Methods Single-nucleotide p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…Our data corroborate these findings in Europeans, strengthening the overall evidence. Xu et al [25], in a recent two-sample MR study using largely the same European GWAS data, confirmed the positive effects of platelet count on both SBP and DBP that we observed. However, they also found an effect in the reverse direction of SBP affecting platelet count.…”
Section: Discussionsupporting
confidence: 89%
“…Our data corroborate these findings in Europeans, strengthening the overall evidence. Xu et al [25], in a recent two-sample MR study using largely the same European GWAS data, confirmed the positive effects of platelet count on both SBP and DBP that we observed. However, they also found an effect in the reverse direction of SBP affecting platelet count.…”
Section: Discussionsupporting
confidence: 89%
“…However, our research did not establish a causal relationship between PLT and stroke. In addition, MPV serves as an indicator of the average platelet size, with elevated levels indicating increased platelet activity and aggregation in patients (11,16). Although no significant correlation between PLT and MPV and stroke was found in this study, the potential causal relationship between PCT and stroke may partly explain the inconsistencies between the results of MPV and PLT and the conclusion of previous studies.…”
Section: Discussionmentioning
confidence: 53%
“…Hypertension can induce thromboembolism and atherosclerosis, leading to damage to target organs (15). The activation and aggregation of platelets are potential factors contributing to the increased risk of thrombosis in patients with hypertension (16)(17)(18). Some studies have indicated a potential correlation between MPV and blood pressure (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…A longitudinal study using the quadratic inference function method found a negative relationship between systolic blood pressure and PDW, but no relationship was found with diastolic blood pressure except in the second quartile in men [20]. A study with participants of European descent and using the multivariate Mendelian randomization method reported a causal relationship between PDW and diastolic and systolic blood pressures, indicating a positive relationship between activated platelets and hypertension [21]. In our study, people in diferent age ranges were investigated, and the use of diferent methods in these studies could be one of the reasons for the results not being the same.…”
Section: Discussionmentioning
confidence: 99%
“…Te results of a longitudinal study in China showed a positive relationship between PLT and diastolic blood pressure [20]. Also, a study estimated the relationship between PLT and hypertension with the Mendelian randomization method, in which univariately, PLT levels were associated with increased blood pressure, and in the multivariate model, after collinearity correction, the efect of PLT on hypertension remained strong [21]. However, contrary to these results, another study compared two hypertensive groups and healthy controls in terms of PLT, PLT was not signifcantly diferent in the two groups, and the duration of hypertension showed a negative correlation with PLT [24].…”
Section: Discussionmentioning
confidence: 99%